Supervision during Resistance Training: A Comparison of Trainer and Trainee Perceptions - James Fisher; Patroklos Androulakis-Korakakis; Jürgen Giessing; Eric Helms; Brad Schoenfeld; Dave Smith; Richard Winett (International Universities Strength and Conditioning Association, 2023)
Background: Resistance training has well-documented health benefits; however, participation and adherence remain overwhelmingly low. Supervision has been evidenced to improve adherence, and produce favourable adaptations compared to unsupervised resistance training. A recent exploratory systematic review and meta-analysis on supervision during resistance training noted a lack of clarity as to the purpose/intent of the supervisor within the body of literature. Methods: An online cross-sectional survey study was conducted in English and distributed primarily across social media platforms and through the authors' personal and professional networks. The aim of the survey was to compare the perceptions of supervision between trainers and trainees. Secondary outcomes included exploratory analyses of the impact of training experience, sex of participant, and comparison based on supervision type. Results: 468 participants completed all elements of the survey (68% male, 32% female). Of which 236 were personal trainers/strength coaches, and 232 were trainees. In brief, descriptive data from the survey suggest that trainers perceived supervision as more important than trainees for the characteristics and variables measured. Females perceived supervision in resistance training as more important than males. Trainees who engage in supervised resistance training reported supervision to be more important compared to those training alone or with a training partner. Technical coaching was reported to be the most important characteristic of supervision. Finally, trainers and trainees engaging in supervised strength training reported lower injury rates compared to those strength training unsupervised or with a training partner. Qualitative data are presented regarding perceptions of how and why supervision should differ based on sex, age, and experience, as well as reporting injury experiences. Conclusion: Our data suggest that the perceived benefits of supervision vary based on population. We posit that the present data have implications for both trainers and trainees, which might serve to strengthen a relationship by aligning roles and realising goals in supervised resistance training. Further, this data might provide insight and prompt future research as to how to engage more people into resistance training.